1971
DOI: 10.1055/s-0038-1653709
|View full text |Cite
|
Sign up to set email alerts
|

Un nouveau Cas d’Anomalie constitutionnelle et familiale du Fibrinogène sans Diathese hémorragique

Abstract: SummaryA new family with congenital dysfibrinogenemia without bleeding tendency has been discovered in Nancy. Identical laboratory abnormalities were found in the mother and son plasma: prolongation of thrombin and reptilase clotting time.The abnormal fibrinogen affects, only a little, the normal plasma fibrinoformation.The functional characterization of the defect is localized in fibrin monomer aggregation. The release of fibrinopeptides is normal.The abnormal fibrinogen showsa) an alteration in glucidic moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1974
1974
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Abnormalities ofthe carbohydrate moiety of the fibrinogen molecule have been described in several of the genetic dysfibrinogenemias, including fibrinogens Nancy and Paris 11 (10). Both fibrinogens Nancy and Paris 11 are reported to have an increased sialic acid content and both are functionally characterized by an abnormality of fibrin monomer polymerization (13,14). We have studied the purified fibrinogen of 12 patients with the dysfibrinogenemia associated with liver disease, and have demonstrated that this abnormal fibrinogen has an increased sialic acid content ranging from 12.7 to 71.4% higher than the normal control.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities ofthe carbohydrate moiety of the fibrinogen molecule have been described in several of the genetic dysfibrinogenemias, including fibrinogens Nancy and Paris 11 (10). Both fibrinogens Nancy and Paris 11 are reported to have an increased sialic acid content and both are functionally characterized by an abnormality of fibrin monomer polymerization (13,14). We have studied the purified fibrinogen of 12 patients with the dysfibrinogenemia associated with liver disease, and have demonstrated that this abnormal fibrinogen has an increased sialic acid content ranging from 12.7 to 71.4% higher than the normal control.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical expression of the defect is variable, ranging from no clinical manifestations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), to bleeding (9,(12)(13)(14)(15)(16)(17)(18)(19)(20) and even thrombotic episodes (14,20,21). Wound dehiscence also has been reported (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…In fibrinogens Bethesda III [17], Baltimore I [18], Paris II [19], Nancy [20] and Philadelphia [2], the abnormality lies in the elution of the first peak, whereas in Paris I [22], the two fibrinogen peaks emerged later than their presumed counterparts.…”
Section: Discussionmentioning
confidence: 99%